Obinutuzumab plus chlorambucil versus ibrutinib in previously untreated chronic lymphocytic leukemia patients without TP53 disruptions: A real-life CLL campus study - Visentin, Andrea; Mauro, Francesca Romana; Catania, Gioachino; Fresa, Alberto; Vitale, Candida; Sanna, Alessandro; Mattiello, Veronica; Cibien, Francesca; Sportoletti, Paolo; Gentile, Massimo; Rigolin, Gian Matteo; Quaglia, Francesca Maria; et al. (Frontiers in Oncology, 2022)
One of the main issues in the treatment of patients with chronic lymphocytic leukemia (CLL) deals with the choice between continuous or a fixed-duration therapy. Continuous ibrutinib (IB), the first-in-class BTK inhibitor, and obinutuzumab-chlorambucil (G-CHL) are commonly used therapies for elderly and/or comorbid patients. No head-to-head comparison has been carried out. Within the Italian campus CLL network, we performed a retrospective study on CLL patients without TP53 disruption treated with IB or G-CHL as first-line of therapy. Patients in the G-CHL arm had a higher CIRS score and a worst renal function. The overall response rates between the G-CHL and IB arms were similar, but more CRs were achieved with G-CHL (p=0.0029). After a median follow-up of 30 months, the progression-free survival (PFS,p=0.0061) and time-to-next treatment (TTNT,p=0.0043), but not overall survival (OS,p=0.6642), were better with IB than G-CHL. Similar results were found after propensity score matching and multivariate analysis. While PFS and TTNT were longer with IB than G-CHL in IGHV unmutated patients (p=0.0190 and 0.0137), they were superimposable for IGHV mutated (p=0.1900 and 0.1380). In the G-CHL arm the depth of response (79% vs 68% vs 38% for CR, PR and SD/PD;p<0.0001) and MRD influenced PFS (78% vs 53% for undetectable-MRD vs detectable-MRD, p=0.0203). Hematological toxicities were common in the G-CHL arm, while IB was associated with higher costs. Although continuous IB provides a better disease control in CLL, IGHV mutated patients and those achieving an undetectable-MRD show a marked clinical and economic benefit from a fixed-duration obinutuzumab-based treatment.